Absenteísmo, presenteísmo e transtornos mentais comuns: o fundo de cena da enfermagem na saúde pública em região de fronteira - Padovani, Edson Edvaldo (2024)
This work is a pioneer in approaching three aspects as a little-explored issues, which subtly become commonplace, being molded as normal in the work of nursing professionals. Existing publications point to a prevalence of common mental disorders, absenteeism and presenteeism among nurses. In the literature we find complaints of intense discomfort in the sense of fear, insecurity, irritability and great discouragement, in other words, significant subjective suffering. The quality of work is compromised, either by excessive demand and low pay, or by health problems of various causes. This affects the work environment, leading to losses in productivity and implications for workers' health. The study aimed to verify the presence of absenteeism, presenteeism and common mental disorders among nurses working in basic health units in Foz do Iguaçu. This is a cross-sectional, descriptive, correlational study with a quantitative approach, was carried out using quantification and statistical techniques. The setting is a trinational border municipality made up of Brazil, Paraguay and Argentina. From the 97 nurses working in the 29 Basic Health Units, 65 (67%) took part. They answered instruments such as the Stanford Presenteeism Scale - 6 (SPS-6) to measure presenteeism; and the Depression, Anxiety and Stress Scale-21 (DASS 21) questionnaire to measure mental disorders. For the absenteeism index, information was collected from the databases of the Human Resources sector and the Occupational Health Directorate (DISO) of Foz do Iguaçu-PR municipal authority. The research was approved by the Human Research Ethics Committee of the State University of Western Paraná. The data collected from the instruments was entered into a Microsoft Office Excel 2010® spreadsheet. The chi-square test and Pearson's correlation were used to relate common mental disorders, absenteeism and presenteeism, adopting a significance level of α= 0.05. The results showed a small group within the normal range (stress 38.5%, anxiety 35.4% and depression 41.5%). There were 40 (61.5%) nurses with stress, 42 (64.6%) with pathological anxiety and 38 (58.4%) with depressive episodes. There was a strong positive correlation between the three sub-scales of the DASS-21 instrument, with p<0.05. The correlation between stress and anxiety was 0.728 (Ic 0.59:0.83); between stress and depression 0.786 (Ic 0.67;0.88) and between anxiety and depression 0.768 (Ic 0.64; 0.85). High presenteeism and better work performance were observed, with 63.1% having a score greater than 18, while 36.9% had a score less than or equal to 18, representing low presenteeism. Absenteeism over the last five years amounted to 126 certificates, with highest average of 152.1 days lost in 2020. The study highlighted a high rate of common mental disorders among nurses. The data suggests that productive hours are lost due to the presenteeistic behavior of the participants. In relation to absenteeism, the research noted a work gap. The conclusion is that there is a need for basic actions in public policies aimed at preventing and caring for the physical and mental health of nursing workers.